Behavioural patterns of university students during the COVID-19 pandemic: A cross-sectional study of the effects of active transportation, uninterrupted sitting time, and screen use on physical activity and sitting time [version 3; peer review: 1 approved, 2 approved with reservations] - Nicolas Jacquemond; Andrés Ladino; Guillaume Chevance; Brice Lefèvre; Gonzalo Marchant (F1000Research)
Background The closure of universities due to the coronavirus disease 2019 (COVID-19) pandemic significantly affected students’ behaviours, particularly regarding physical activity, sitting time, and screen use. This study aimed to determine the effect of active transportation duration, uninterrupted sitting time, and screen time to study on physical activity and sitting time during the confinement. Methods This was a cross-sectional study based on data collected via an online questionnaire for university students during the second confinement in France (between October and December 2020). The questionnaire assessed physical activity and sedentary behaviour, and contained questions about modes of transport, and perception of uninterrupted sitting time and screen time to study prior to confinement and during confinement. Participants (N=2873) completed the International Physical Activity Questionnaire (IPAQ) in an average time of around 15 minutes, after providing digital informed consent. Multiple regression models assessed how time duration of active transportation, uninterrupted sitting time, and screen time studying increased or reduced confinement effects on physical activity and sitting time. Results The regression models showed that physical activity decreased during confinement for students who engaged in more prolonged periods of active transportation prior to confinement. Moreover, the perception of long, uninterrupted sitting time and high screen time prior to confinement significantly increased sitting time during confinement. Students who adopted the most active transport time prior to confinement were the least likely to increase their screen time during confinement. Conclusions Confinement reduced physical activity levels and increased sitting time, mainly among students who adopted active transport and accumulated longer uninterrupted sitting time prior to confinement. Students who combined-long periods of uninterrupted sitting time with high screen use could be a riskier profile for health. Analysis of physical activity time and sitting position should include its accumulation patterns.